Coagulation removal of microplastics from wastewater by magnetic magnesium hydroxide and PAM. (October 2021) - Zhang, Yutao; Zhao, Jianhai; Liu, Zhaoyang; Tian, Sufeng; Lu, Jingfang; Mu, Rong; Yuan, Hongying
Abstract: Recently, microplastics, a new type of pollutant, have attracted much attention around the world. In this study, a magnetic magnesium hydroxide coagulant (MMHC) was produced by adding magnetic particles of Fe3 O4 during the formation of Mg(OH)2 to remove polyethylene from wastewater, which easily floats on the water surface and is a major component of microplastics. The removal efficiency of microplastics after coagulation was compared with the traditional magnesium hydroxide coagulant (MHC). In addition, three magnetic magnesium hydroxides were prepared by changing the ratio of Mg 2+ to OH − when magnesium hydroxide was formed. Scanning electron microscopy (SEM) images showed the surface morphology of three types of magnetic magnesium hydroxide and Fourier transform infrared spectroscope (FTIR) described the formation of new bonds during the formation of magnetic magnesium hydroxide. The results showed that among the three types of MMHC, when Mg 2+ :OH − was 1:1, the removal efficiency of microplastics reached the highest of 87.1%, which was 14.7% higher than that of MHC only. In addition, when magnetic magnesium hydroxide was added with 120 mg/L of Fe3 O4 and 200 mg/L of Mg(OH)2, the removal efficiency of microplastics would increase to about 92% when accompanied by the addition of 4 mg/L of non-ionic polyacrylamide (PAM). However, in the range of pH 5–9, the removal efficiency of microplastics did not change significantly, and charge neutralization occurred in the coagulation process. The particle size of the two kinds of coagulants shifted from large to small with time aging, while the flocs generated by the two coagulants showed an opposite trend. Graphical abstract: Unlabelled Image Highlights: Three different mass ratios of magnetic magnesium hydroxide were prepared. The aging time of coagulant has no significant influence on removal efficiency. Charge neutralization and sweep flocculation occurred during coagulation process. Microplastics removal efficiency by magnetic magnesium hydroxide is 92%.